PHILOSOPHICAL PROBLEMS OF SHEVCHENKO STUDIES IN THE UNIVERSITY OF KYIV IN THE END OF THE 19TH – BEGINNING OF THE 20TH CENTURIES - Смольницька, О. О. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the philosophical problems of Taras Shevchenko works which given by literature scientists of the University of Kyiv are analyzed. The different Shevchenko studies discourses are examined, the unconsciousness artistic factor and esthetical doctrine are analyzed. The problem of poetry like mythmake is emphasized.